The Role of Customary Leaders as Ḥakam in Resolving Divorce: A Case Study in Kuta Alam Subdistrict, Banda Aceh City - Nurdin, Ridwan; Abdullah, Muslem; Fahmi, Zakiyul; Darna, Andi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Divorce in households can occur due to several factors, such as economic factors, ongoing arguments, and domestic violence. Therefore, an alternative solution in such a situation is necessary by involving the role of the village customary leaders as a ḥakam (peacemaker). The effectiveness of the role of the village customary leaders as a ḥakam must fulfill five aspects: purpose, strategy, policy, planning, and implementation. In this study, the aim was to examine the role of the village customary leaders as a ḥakam in resolving divorce in Kuta Alam Subdistrict, Banda Aceh City and the effectiveness of the role of the village customary leader as a ḥakam in resolving divorce in Kuta Alam Subdistrict, Banda Aceh City. The study used a qualitative research method, using a normative sociological approach, and collected the data by means of interviews and document study. The results showed that village customary leaders such as ḥakam play the role of mediators in marital disputes, in which they investigated and found the roots of the problems with the hope that the disputed could be reconciled and reunited in their households. Further, the role of the village customary leaders as a ḥakam has been considered effective as seen from several peace processes carried out. However, some cases of conflict have not been resolved because some parties demand settlement in court. The study suggests that village customary leaders as ḥakam need to pay attention to the aspect of legal force in handling divorce and that the village institution should prepare administrative staff in the deliberation process